INFLUENCE OF PRICE AND PRODUCT QUALITY ON CONSUMER SATISFACTION WITH GINASTEL TEA WITH SERVICE QUALITY AS A MODERATION VARIABLE (Case Study of Ginastel Tea Consumers in the Jebres District Surakarta City) - Olivia, Reta; Erni Widiastuti; Sukesi (LPPM STIE EKA PRASETYA, 2025)
The goal of this study was to examine the effect of pricing and product quality on Ginastel Tea consumer satisfaction with service quality as moderation (Study of Ginastel Tea consumers in the Jebres District Area, Surakarta City). This research is quantitative research. The demographic in this study are consumers who have purchased Ginastel Tea at least twice directly at the Jebres District Outlet. The sample used in this research was 100 respondents. The data was gathered via a questionnaire that was handed out just in front of the Jebres District Outlet, and the sample methodology employed was the purposive sampling technique. The following tests are utilised in data analysis: determinant (R2), t-test, multiple linear regression, descriptive analysis, validity, and reliability. This study used SPSS 26 for Windows to process the data. Consumer Satisfaction (Y) is positively and significantly affected by Price (X1), Product Quality (X2), and Service Quality (Z), according to the t test results. Product quality is 4.812, service quality is 3.229, and the pricing ttable value is 4.967. When comparing the effects of pricing and product quality on customer satisfaction, the moderation test found that service quality moderated the relationship.